Surface modification of microporous polycaprolactone (PCL) microcarrier to improve microcarrier biocompatibility - Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Arifin, Mohd Azmir; Mel, Maizirwan; Mohd. Salleh, Hamzah (International Institute for Halal Research and Training (INHART), IIUM, 2018)
Oil/water emulsion solvent evaporation method was employed to fabricate PCL microcarriers. The surface of these microcarriers were modified with porogen, UV/O3 system and gelatin. The porous network channels were generated inside the microcarrier by introducing camphene. The average pore size of 11.74±8.32 μm was obtained with the concentration of 20% (w/v) of camphene. The porous PCL microcarrier was further tailored with gelatin through surface treatment with UV/O3 system and gelatin immobilization. Vero cells attach and proliferate well on the gelatin coated porous PCL microcarrier with maximum cell number of 3.90 x 105 cells/ml as compared to cell proliferation on UV/O3 treated porous PCL microcarrier (1.83 x 105 cells/ml). The developed halal microcarrier may be potentially applicable as a cell delivery scaffold for cell tissue culture and tissue engineering application